2023
DOI: 10.1002/mas.21856
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of mRNA therapeutics

Abstract: Therapeutic messenger RNAs (mRNAs) have emerged as powerful tools in the treatment of complex diseases, especially for conditions that lack efficacious treatment. The successful application of this modality can be attributed to its ability to encode entire proteins. While the large nature of these molecules has supported their success as therapeutics, its extended size creates several analytical challenges. To further support therapeutic mRNA development and its deployment in clinical trials, appropriate metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 141 publications
0
3
0
Order By: Relevance
“…Purity assessment by IP-RPLC typically involves high column temperature and the use of an ion-pairing agent in combination with an organic solvent, while integrity determination by CGE involves the use of high quantities of a denaturing agent (e.g., formamide or 4–8 M urea under nonaqueous conditions). 8 In both methods, denaturing conditions improve the mRNA separation by disrupting base-pairing and base-stacking interactions. mRNA is thus linearized, enabling sharper peaks to be separated and eluted.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Purity assessment by IP-RPLC typically involves high column temperature and the use of an ion-pairing agent in combination with an organic solvent, while integrity determination by CGE involves the use of high quantities of a denaturing agent (e.g., formamide or 4–8 M urea under nonaqueous conditions). 8 In both methods, denaturing conditions improve the mRNA separation by disrupting base-pairing and base-stacking interactions. mRNA is thus linearized, enabling sharper peaks to be separated and eluted.…”
Section: Resultsmentioning
confidence: 99%
“…Several analytical methods are commonly used for mRNA characterization and are employed in quality control (QC) environments to support batch release and stability and assess critical quality attributes (CQAs) at different stages of the drug life cycle, including production and storage. , Purity is usually assessed by ion-pair reversed-phase liquid chromatography (IP-RPLC) by measuring product-related impurities, such as short mRNA fragments, while integrity is usually confirmed by determining mRNA length by capillary gel electrophoresis (CGE). , As an alternative, Raffaele et al demonstrated the value of using on-chip capillary electrophoresis to determine the purity and integrity of 2000-nucleotide (nt) mRNA in lipid nanoparticle vaccines . Recently, considerable efforts have been made to improve the separation, sensitivity, applicability, and turnaround times of the HPLC-based methods.…”
Section: Introductionmentioning
confidence: 99%
“…The purity of mRNAs, including dsRNA and uncapped RNA content, has recently been identified as one of the most important factors for their therapeutic applications, particularly in anti-cancer and protein replacement approaches. 50 Therefore, we believe that AvantCap can provide a significant improvement in this area.…”
Section: Discussionmentioning
confidence: 98%